French Philosophy and Social Theory - Rendtorff, Jacob Dahl. author. (orcid)0000-0001-9021-4720 Link aut Link
VII, 315 p.
Keywords: This book demonstrates how the conceptual resources of contemporary French philosophy from the early 20thCentury to the present day can be applied to give us new perspectives on business ethics and the ethics of organizations. In providing an overview of possible applications,the book covers a wide range of philosophers, philosophical movements and perspectives, and provides detailed analyses of core materials relevant to business ethics. It explores and analyzes French philosophy, taking into account phenomenology,existentialism, French epistemology, structuralism, post-structuralism,deconstruction and postmodernism as well as recent discussions of philosophy of organizations and management. Each chapter contains suggestions for further reading and educational illustrations of possible applications to the mainstream business ethics and ethics of organization literature.